2020
DOI: 10.1038/s41598-020-77097-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood-derived extracellular vesicles isolated from healthy donors exposed to air pollution modulate in vitro endothelial cells behavior

Abstract: The release of Extracellular Vesicles (EVs) into the bloodstream is positively associated with Particulate Matter (PM) exposure, which is involved in endothelial dysfunction and related to increased risk of cardiovascular disease. Obesity modifies the effects of PM exposure on heart rate variability and markers of inflammation, oxidative stress, and acute phase response. We isolated and characterized plasmatic EVs from six healthy donors and confirmed a positive association with PM exposure. We stratified for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…EVs derived from PM-exposed alveolar epithelial cells fueled inflammatory signaling via inhibitor of the nuclear factor kappa alpha (IκBα)–nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)–vascular cell adhesion protein 1 (VCAM1) axis [ 52 ]. Nevertheless, EVs shed after PM exposure could also mediate crosstalk between EC-immune cells to cope with the inflammatory assault [ 53 ], a response impaired in overweight subjects at increased cardiovascular risk [ 54 ].…”
Section: Evs As Pathophysiological Drivers Of Atherothrombosismentioning
confidence: 99%
“…EVs derived from PM-exposed alveolar epithelial cells fueled inflammatory signaling via inhibitor of the nuclear factor kappa alpha (IκBα)–nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)–vascular cell adhesion protein 1 (VCAM1) axis [ 52 ]. Nevertheless, EVs shed after PM exposure could also mediate crosstalk between EC-immune cells to cope with the inflammatory assault [ 53 ], a response impaired in overweight subjects at increased cardiovascular risk [ 54 ].…”
Section: Evs As Pathophysiological Drivers Of Atherothrombosismentioning
confidence: 99%
“…In two of these studies, human exposure to PM was characterized by regional air monitors and EVs were isolated from human plasma samples. These studies both showed that EVs were released in a greater concentration after short‐term exposure to high‐level PM compared to low‐level PM after 24 h (Bonzini et al, 2017; Rota et al, 2020). Both studies also identified overweight individuals as a particularly susceptible population.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, both adverse and protective effects have been observed. For example, EVs isolated from human plasma with varying PM exposure levels were used to treat primary endothelial cells (Rota et al, 2020). EVs isolated from human plasma with high PM exposure increased endothelial activation, while EVs isolated from human plasma with low PM exposure decreased endothelial activation (Rota et al, 2020).…”
Section: Landscape Of Existing Literature Evaluating Environmental Co...mentioning
confidence: 99%
“…In this context, plasmatic extracellular vesicles (EVs), which have a critical role in the cross-talk between cells [12][13][14], are a good candidate as mediators of the airway allergic process enhancement [15,16]. Moreover, EVs strongly contribute to the modulation of the inflammatory response after PM exposure, thus enforcing this hypothesis [17][18][19]. Interestingly, EVs represent a conserved communication mechanism between domains of life; indeed they can be released by human (i.e., hEVs) and bacterial cells (i.e., bEVs) into the bloodstream [13,14,20].…”
Section: Introductionmentioning
confidence: 94%
“…Quantitative multiparameter analysis of flow cytometry data (expressed as 10 3 for 1 mL of plasma) was run using FlowJo software (Tree Star, Inc., Ashland, OR, USA). Antibody gating strategies are reported in the supplementary information (Supplementary Figures S1-S4) and were previously described [17,35].…”
Section: Flow Cytometry On Evsmentioning
confidence: 99%